Fabrication of the Trapezoidal electrodes and Electrets material for electrostatic energy harvester - Ahmad, M.R. (2013)
Conversion of the mechanical vibration into electrical energy has been found feasible with MEMS (Micro-Electro-Mechanical-System) electrostatic energy harvesting method. The electrostatic energy harvesting device is fabricated on a silicon wafer for use on miniaturize applications. This paper presents the detail fabrication processes of the electrostatic energy harvester components, i.e. the Trapezoidal electrodes and Electrets. The trapezoidal electrodes structure comprises of the seismic mass, serpentine beams and Aluminum electrodes whereas the electrets is made up of Silicon Dioxides (SiO 2). The energy harvester components are designed with Cadence Virtuoso software and later fabricated at the wafer foundry leveraging the 0.35 Î¼m CMOS processes on 200 mm silicon wafers. The trapezoidal electrodes and electrets fabrications went through seven and two masking steps respectively. Performance of the electrets material are evaluated with Corona charging method. Characterization results show that the CVD oxide exhibits good charge retention capability, hence is recommended for application as electrets material on the vibration-based electrostatic energy harvester. Â© 2013 IEEE.